Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Transmission Associated With an Indoor Music Event That Required Proof of Full Vaccination Against Coronavirus Disease 2019 (COVID-19) Prior to Entry—Seattle, July 2021 . (20th June 2022) - Roskosky, Mellisa; Moni, Gwen; Kawakami, Vance; Lambert, Joanie; Brostrom-Smith, Claire; Whitney, Holly; Phu, Amy; Look, Jennifer; Pallickaparambil, Aley; Kay, Meagan; Duchin, Jeff
Abstract: In July 2021, Public Health–Seattle & King County investigated a coronavirus disease 2019 (COVID-19) outbreak at an indoor event intended for fully vaccinated individuals, revealing unvaccinated staff, limited masking, poor ventilation, and overcrowding. Supporting businesses to develop and implement comprehensive COVID-19 prevention plans is essential for reducing spread in these settings.